The Collaborative Teacher Inquiry Project: A Purposeful Professional Development Initiative - Jao, Limin; McDougall, Douglas (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
The transition from Grade 8 to Grade 9 is particularly difficult for students who were not very successful in mathematics in Grade 8. Research into ways to improve this transition as well as improve the teaching practices at the Applied level will be helpful for teachers, administrators, and policy makers. The Collaborative Teacher Inquiry Project was a professional development initiative that brought together educators from nine schools across four neighbouring school districts in Ontario seeking to improve their Grade 9 Applied Mathematics program. As part of the Collaborative Teacher Inquiry Project, participants attended topic-specific workshops based on schools’ goals for professional growth and had opportunities to collaborate with other participants to create and share teaching materials for the Grade 9 Applied Mathematics course. Qualitative data from teacher interviews and written reflections indicate that the teachers felt that a mixture of collaboration and professional development made this project successful. Teachers also reported that the Collaborative Teacher Inquiry Project motivated further collaboration at the school and district level.